Learning from the past, imagining the future : reflections from a political life = Apprendre du passé, façonner l'avenir : réflexions sur une vie politique - Rae, Bob (Symons Medal series., 2023)
"The Symons Medal--one of Canada's most prestigious honours--recognizes an individual who has made an exceptional contribution to Canadian life. The 2020 Symons Medal was awarded to Mr. Bob Rae, P.C., C.C., O.Ont, Q.C. Mr. Rae is the 20th Medallist in this series, following a formidable line of recipients. Hon. Rae's lecture is Learning from The Past, Imagining the Future: Reflections from a Political Life. Throughout the address, published in a bilingual book format, he explores such themes as Canada's improbable origins as a nation; post-war emergence onto the global stage; active membership within the United Nations; and the significance of the ever-evolving Canadian constitution--a "living tree document." Welcoming remarks were made by the Honourable Premier Dennis King, while the official response was delivered by the Honourable Roy Romanow, PC, OC, SOM, QC. Hon. Rae is the 2020 recipient in part for his many years of work on humanitarian issues, most recently the Rohingya Refugee crisis, as well as his time focusing on indigenous issues and his decades of public service and teaching. He has always been deeply involved in the political life of Canada--as MP, former premier of Ontario, and interim leader of the federal Liberal Party. The Symons Medal and Lecture Series is named in honour of Professor Thomas H.B. Symons, a long-time supporter of Confederation Centre and a Board Governor. Held each fall, the medal ceremony and its associated lecture offer a national platform for an eminent Canadian to discuss the nation's current state, shared histories, and future prospects using themes related to their professional pursuits. The award is presented at Confederation Centre of the Arts--Canada's living monument to Canadian Confederation--in honour of the meetings of the Fathers of Confederation, who first gathered at Province House National Historic Site in the fall of 1864."--